Randomized comparison of precut papillotomy versus an endoscopic ultrasound-guided rendezvous procedure for difficult biliary access in malignant distal biliary obstruction - Dhir, Vinay; Singh, Vivek Kumar; Dalal, Ankit; Patil, Gaurav Kumar; Maydeo, Amit (Endoscopy, 2025)
Difficult biliary cannulation (DBC) is a marker for prolonged procedure time and a higher rate of adverse events (AEs) during endoscopic retrograde cholangiopancreatography (ERCP). We previously showed that endoscopic ultrasound-assisted rendezvous (EUS-RV) procedures had a higher single-session success rate than precut papillotomy (PCP) in cases of DBC. The present randomized study aimed to compare the technical success and AE rates of the two approachesThis was an open-label randomized controlled trial in a tertiary care setting. Patients with malignant distal biliary obstruction (MDBO) and DBC were enrolled. The patients were randomized to PCP with a needle-knife or EUS-RV. The primary outcome was technical success; secondary outcomes were the AE rate, procedure duration, and length of hospital stay (LOS).208 patients were enrolled, 104 in each group. There were no statistically significant differences in technical success (93.3% PCP vs. 97.1% EUS-RV; P = 0.33; odds ratio [OR] 0.4, 95%CI 0.1–1.6) and overall AE rate (11.5% PCP vs. 5.8% EUS-RV; P=0.14; OR 0.5, 95%CI 0.8–5.9). Pancreatitis was higher in the PCP group (8.7% vs. 1.9%; P=0.06; OR 4.8, 95%CI 1.0–22.9). The mean duration of the procedure was significantly higher for EUS-RV (47 vs. 27 minutes; P<0.001). LOS was similar in the two groups (1.2 PCP vs. 1.1 days EUS-RV; P=0.25).Both PCP and EUS-RV have comparable rates of success, AEs, mortality, and LOS. EUS-RV could be used as an alternative to PCP in patients with MDBO and DBC.